Organic carbon remobilized from thawing permafrost is resequestered by reactive iron on the Eurasian Arctic Shelf. Issue 19 (14th October 2015) - Salvadó, Joan A.; Tesi, Tommaso; Andersson, August; Ingri, Johan; Dudarev, Oleg V.; Semiletov, Igor P.; Gustafsson, Örjan
Abstract Given the potential for permafrost carbon (PF/C)‐climate feedbacks in the Siberian‐Arctic land‐ocean system, there is a need for understanding the fate of thawed‐out PF/C. Here we show that the sequestration of OC by reactive iron (OC‐Fe) ranges between 0.5 and 22% on the Eurasian Arctic Shelf, with higher values in the Kara Sea (KS) (18 ± 6%) and the Laptev Sea (LS) (14 ± 4%). The Δ14C/δ13C signatures of the OC‐Fe are substantially older and more terrestrial than the bulk sediment OC in the LS but younger and more dominated by marine plankton sources in the East Siberian Sea (ESS). Statistical source apportionment modeling reveal that reactive iron phases resequestered 15 ± 5% of thawing PF/C in the LS and 6.4 ± 5% in the ESS, derived from both coastal erosion of ice complex deposit and thawing topsoil. This Fe‐associated trap of PF/C constitutes a reduction of the degradation/outgassing and thus also an attenuation of the PF/C‐climate feedback.